THE RELEVANCE OF THE ETHICS OF VULNERABILITY IN BIOETHICS - DELGADO RODRIGUEZ, JANET (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2017)
The concept of vulnerability is central to current developments in bioethics, not only because of its analytic nature, but also due to its capacity for criticism. However, this concept has not been sufficiently developed, neither in the area of moral philosophy nor in bioethics. For this reason, it is necessary to define and analyze the conceptual framework in which the notion of vulnerability has been developed within the scope of bioethics. Thus, the purpose of this paper is to indicate how the concept of vulnerability in the field of bioethics has been developed and what the main problems that derive from this approach are. Secondly, the paper analyzes some of the main philosophical approaches that I consider should be articulated in the expansion of a critical bioethics approach focused on the notion of vulnerability. To address this issue, I analyze the reflections that we find in the work of Martha Fineman, emphasizing the main relevant aspects for bioethics. Finally, I highlight the main implications of a theory of vulnerability for bioethics.